A New Sensitive Sensor for Simultaneous Differential Pulse Voltammetric Determination of Codeine and Acetaminophen Using a Hydroquinone Derivative and Multiwall Carbon Nanotubes Carbon Paste Electrode. (6th April 2015) - Garazhian, Elahe; Shishehbore, M. Reza
Abstract : A new sensitive sensor was fabricated for simultaneous determination of codeine and acetaminophen based on 4-hydroxy-2-(triphenylphosphonio)phenolate (HTP) and multiwall carbon nanotubes paste electrode at trace levels. The sensitivity of codeine determination was deeply affected by spiking multiwall carbon nanotubes and a modifier in carbon paste. Electron transfer coefficient, α, catalytic electron rate constant, k, and the exchange current density, j 0, for oxidation of codeine at the HTP-MWCNT-CPE were calculated using cyclic voltammetry. The calibration curve was linear over the range 0.2–844.7  μ M with two linear segments, and the detection limit of 0.063  μ M of codeine was obtained using differential pulse voltammetry. The modified electrode was separated codeine and acetaminophen signals by differential pulse voltammetry. The modified electrode was applied for the determination of codeine and acetaminophen in biological and pharmaceutical samples with satisfactory results.